2023
DOI: 10.1002/hbm.26205
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Alzheimer's disease and frontotemporal dementia using machine learning with cross‐sectional and longitudinal magnetic resonance imaging data

Abstract: Alzheimer's disease (AD) and frontotemporal dementia (FTD) are common causes of dementia with partly overlapping, symptoms and brain signatures. There is a need to establish an accurate diagnosis and to obtain markers for disease tracking. We combined unsupervised and supervised machine learning to discriminate between AD and FTD using brain magnetic resonance imaging (MRI). We included baseline 3T‐T1 MRI data from 339 subjects: 99 healthy controls (CTR), 153 AD and 87 FTD patients; and 2‐year follow‐up data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…While these are promising, at present, literature mostly involves cross-sectional studies in AD. Examples are speech-based artificial intelligence (AI) applications predicting cognitive decline ( Fristed et al, 2022 ), biometric measures (e.g., skin conduction, pupillometry and eye-tracking patterns) reflecting social-emotional and/or linguistic deficits ( Mendez et al, 2018 ; Singleton et al, 2022 ; El Haj et al, 2024 ), AI-based imaging algorithms for longitudinal brain mapping ( Pérez-Millan et al, 2023 ), and proteomics technology detecting protein profiles ( Katzeff et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these are promising, at present, literature mostly involves cross-sectional studies in AD. Examples are speech-based artificial intelligence (AI) applications predicting cognitive decline ( Fristed et al, 2022 ), biometric measures (e.g., skin conduction, pupillometry and eye-tracking patterns) reflecting social-emotional and/or linguistic deficits ( Mendez et al, 2018 ; Singleton et al, 2022 ; El Haj et al, 2024 ), AI-based imaging algorithms for longitudinal brain mapping ( Pérez-Millan et al, 2023 ), and proteomics technology detecting protein profiles ( Katzeff et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since clinical trials intend to intervene in early and intermediate stages, characterized by relatively diverse behavioral symptoms, behavioral inflection points should be taken into account. For instance, a crescendo-decrescendo pattern, including dominating apathy (measured with DAS or sub scores of FBI or CBI) in late stages, (Fristed et al, 2022), biometric measures (e.g., skin conduction, pupillometry and eye-tracking patterns) reflecting social-emotional and/or linguistic deficits (Mendez et al, 2018;Singleton et al, 2022;El Haj et al, 2024), AI-based imaging algorithms for longitudinal brain mapping (Pérez-Millan et al, 2023), and proteomics technology detecting protein profiles (Katzeff et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning, tailored for intricate multivariate data, holds promise as an adjunct in the diagnostic process by offering decision support [25]. Previous studies have use machine learning algorithms to classify between the subtypes of dementia [25][26][27] and subtypes of FTD [28,29] in structural MRI. The accuracy of machine learning model between subtypes of FTD was ranged from 0.7-0.94.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence supports the role of machine learning (ML) techniques using brain MRI (15)(16)(17) to support the clinical diagnosis of these two dementias (18)(19)(20)(21)(22). Many studies have shown that a support vector machine (SVM) with neuroimaging data differentiates AD or FTD patients from healthy controls (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence supports the role of machine learning (ML) techniques using brain MRI (15)(16)(17) to support the clinical diagnosis of these two dementias (18)(19)(20)(21)(22). Many studies have shown that a support vector machine (SVM) with neuroimaging data differentiates AD or FTD patients from healthy controls (22)(23)(24)(25)(26)(27). However, fewer studies exist on the differential diagnosis of these two dementias, even though the clinical symptoms of FTD and AD can display a substantial overlap between them (28-30).…”
Section: Introductionmentioning
confidence: 99%